Satisfaction Level of Livestock Owner towards Delivery of Veterinary Services - Chaturvedani, A. K.; Lal, Niranjan; Dhruw, Kalpana (International Journal of Bio-resource and Stress Management, 2016)
A study was conducted with exploratory research design in Bilaspur district of Chhattisgarh (India) to assess satisfaction level of the livestock owner about delivery of veterinary services, provided by department of animal husbandry. The department of animal husbandry deals with welfare of livestock and is responsible for matters related to livestock treatment, production, protection and improvement of breeding stocks, and dairy development. Information was collected with the help of a pretested structured interview schedule from 180 livestock owners, who had at least two milch animals at the time of investigation. Large proportion of livestock owners (45.56%) had medium level of satisfaction with state veterinary services followed by low and high category of satisfaction, 38.33% and 16.11% respectively. Livestock owners were found ‘very satisfied’ with efficiency and effectiveness of treatment i.e. compatibility in performance with minimum expenditure of time and effort to treatment of animals, information about disease outbreak and vaccination of animal whereas, ‘dissatisfied’ with Consultancy services on animal husbandry, veterinary services at village level, awareness campaign regarding diseases, insurance of animals, infertility camps and post-mortem. There was vast difference in level of satisfaction among livestock owners which may be overcome by reducing coverage area under each hospital. Hence, fulfilling the livestock owners’ demand by timely satisfactory veterinary service delivery in cost effective manner is very important for the success of veterinary services.